2007
DOI: 10.1002/chin.200736206
|View full text |Cite
|
Sign up to set email alerts
|

Quercinol, an Antiinflammatory Chromene from the Wood‐Rotting Fungus Daedalea quercina (Oak Mazegill).

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…13 C{ 1 H} NMR (CDCl 3 , 100 MHz): δ 154. 6,152.1,132.0,128.8,128.4,122.5,116.4,114.8,87.2,84.4,57.7,55.8. MS (rel.…”
Section: -{[3-(4-chlorophenyl)prop-2-yn-1-yl]oxy}naphthalene (1e)mentioning
confidence: 99%
See 1 more Smart Citation
“…13 C{ 1 H} NMR (CDCl 3 , 100 MHz): δ 154. 6,152.1,132.0,128.8,128.4,122.5,116.4,114.8,87.2,84.4,57.7,55.8. MS (rel.…”
Section: -{[3-(4-chlorophenyl)prop-2-yn-1-yl]oxy}naphthalene (1e)mentioning
confidence: 99%
“…Chromenes and their derivatives represent an important structural unit found in several natural products 1 and compounds with important biological activities, 2 such as anticancer, 3 antidiabetic, 4 cardiovascular, 5 and anti-inflammatory activity. 6 Due to the growing importance and utility of the chromenes, different methodologies have been reported for their preparation. 7 The electrophilic cyclization reaction of propargylic aryl ethers has been highly effective for synthesizing 3,4-disubstituted 2H-chromenes as reported by Larock and co-workers 8 in the reaction with electrophiles I 2 , ICl, and PhSeBr using nitromethane or dichloromethane as solvent (Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…D. quercina have been reported to contain exopolysaccharides of α-linked mannan and αand β-linked glucan from mycelia culture (Manzoni and Rollini, 2001). It also contains ergosterol (ergosta-7, 22-dien-3β-ol), ergosterol peroxide and 3α-carboxyacetoxyquercinic acid (Turner et al, 1983;Adam et al, 1967), 16-O-acetylpolyporenic acid C, 16αacetoxy-24-methylene-3-oxolanost-8-en-21-oic acid, (+)-24-methylene-3,23-dioxolanost-8-en-26-oic acid, (+)-3b,12b-dihydroxy-24-methyl-23-oxolanost-8-en-26-oic acid and 12b,23epoxy-3a,23-dihydroxy-24-methyllanost-8-en-26-oic acid (Konig et al, 2000), and quercinol, the latter being found to have antiinflammatory activity (Gebhardt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%